The Voice of Veterans With Mild Traumatic Brain Injury: A Community Engagement Project. - Krause-Parello, Cheryl A.; Rossiter, Alicia Gill; Kremer, Abigail; Whitfield, Miriam; Hibler, David; Glenny, John T.; Borah, Elisa; Garvin, Jane; Omslaer, Joy; Arora, Anil; Lindsay, John; Gliba, Brian; et al. (Health & Social Care in the Community, 2025)
This patient‐centered outcome research (PCOR) engagement project, Mind Over Matter (M.O.M.), was driven by veterans and key stakeholders, employing a successful design methodology from prior projects using think tank meetings (TTMs). Focusing on mild traumatic brain injury (mTBI), the project aimed to enhance PCOR by engaging veterans and caregivers, building capacity, and fostering collaboration with researchers to advance PCOR and comparative effectiveness research (CER). The project's structure involved creating M.O.M. units in four states, training members as PCOR and CER partners, building competencies of veterans with mTBI and caregiver stakeholders, understanding healthcare information preferences, and promoting collaborative relationships. Key steps included creating state units, training members, building competencies, understanding communication preferences, and promoting collaboration. The project also aimed to develop a Roadmap for Research on TBI, including future CER questions. The project utilized virtual TTMs organized around TBI domains, involving 210 participants, including veterans and various stakeholders. The M.O.M. team used field note templates to guide the discussion of the veterans and community stakeholders during the virtual TTMs. The field note templates were organized by domains: attention, memory sequencing, problem solving, and executive functioning. Each domain addressed TBI symptom areas that include thinking/remembering, physical, emotional/mood, and sleep. The project successfully fostered collaboration, skill‐building, and engagement among veterans and stakeholders in the context of PCOR and CER, contributing to a comprehensive understanding and research roadmap to better address mTBI and its impact on veterans.